1974
DOI: 10.1001/archinte.1974.00320140059006
|View full text |Cite
|
Sign up to set email alerts
|

Recent Life Changes, Myocardial Infarction, and Abrupt Coronary Death

Abstract: Recent life-change data were gathered from 279 survivors of documented myocardial infarctions and from 226 cases of abrupt coronary death in Helsinki. In nearly half of the infarction cases, recent lifechange data were also collected through a separate interview of spouses. Spouses provided the life-change data for all coronarydeath victims. In all but one group of subjects, marked elevations in magnitude of life changes during the six months immediately prior to infarction or death were seen, compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
3

Year Published

1974
1974
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(24 citation statements)
references
References 10 publications
1
20
0
3
Order By: Relevance
“…In one study, marked elevations in Recent Life Change scores were seen for most cases of MI or sudden cardiac death during the 6-month period preceding these events. 152 Similar confirmations of increased life stress before cardiac events can be extended to specific cohorts, ranging from healthy middle-aged men 153 to patients presenting with acute myocardial infarction. 154 …”
Section: Chronic and Subacute Life Stressmentioning
confidence: 67%
“…In one study, marked elevations in Recent Life Change scores were seen for most cases of MI or sudden cardiac death during the 6-month period preceding these events. 152 Similar confirmations of increased life stress before cardiac events can be extended to specific cohorts, ranging from healthy middle-aged men 153 to patients presenting with acute myocardial infarction. 154 …”
Section: Chronic and Subacute Life Stressmentioning
confidence: 67%
“…A number of anthropological and biomedical studies suggest a link between psychological stress and sudden death (e.g. Brodsky et al 1987;Cannon 1942;Engel 1971;Greene, Goldstein, and Moss 1972;Lown, Verrier and Corbalan 1973;Ornstein and Swencionis 1990;Rahe et al 1974. ) In the medical anthropological and ethnomedical literature, the notion of beliefs playing a significant role in illness causation (nocebo effect) or its remedy (placebo effect) is widely held (Hahn and Kleinman 1983:3,16;Ornstein andSwencionis 1990, Scheper-Hughes andLock 1987).…”
Section: The Nightmare As the Trigger For Hmong Sundsmentioning
confidence: 99%
“…Rahe et al (6) found marked eleva tions in magnitude of life changes during 6 months immediately prior to abrupt coronary death. Holmes (5) has recently argued convincingly of the lethal con sequences of the expectation of death under circumstances of crisis, disease, living dangerously, old age, and sin.…”
mentioning
confidence: 97%
“…Studies of the psychosocial determinants of death have focused on the causative roles of sudden emotional shock (1 ,2 ), bereavement (3,4), crisis (5), increased magnitude of life change events (6), and self-prediction (7). Engel (1) described a reaction to crisis he called giving up-given up, which caused death in healthy or sick individuals at any age.…”
mentioning
confidence: 99%